2001
DOI: 10.1007/s100380170012
|View full text |Cite
|
Sign up to set email alerts
|

Search for active endogenous retroviruses: identification and characterization of a HERV-E gene that is expressed in the pancreas and thyroid

Abstract: To elucidate possible physiological functions of human endogenous retroviruses (HERVs) and their role in the pathogenesis of human diseases, we have developed a strategy to identify transcriptionally active HERV genes. By this approach, we have identified and isolated an active HERV-E gene that was mapped to 17q11. Although the gene was predicted to produce no intact viral particles due to the presence of stop codons, long open reading frames were retained in each gag and pol region. Northern blot analyses rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…The LTRs of HERV-E contain a promoter known to affect transcription of several cellular genes. Moreover, HERV-E transcripts have been seen in both normal and diseased tissues (52,65). To retrieve HERV-E(4-1) Env-encoding sequences, the same type of TBLASTN search that was initially made with ERV3 Env was also made with HERV-E Env.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The LTRs of HERV-E contain a promoter known to affect transcription of several cellular genes. Moreover, HERV-E transcripts have been seen in both normal and diseased tissues (52,65). To retrieve HERV-E(4-1) Env-encoding sequences, the same type of TBLASTN search that was initially made with ERV3 Env was also made with HERV-E Env.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In a broad assay on transcription profiles of HERV-H and HERV-W in different cell lines, the steroidresponsive breast cancer cell line T47D showed a high rate of HERV transcription; in particular, it was the only cell line with high expression of the HERV-F-RD pol gene ). Studies investigating HERVs in different tissue samples showed that adrenal cortex is a preferential site for ERV-9, which is expressed also in the medulla, HERV-R (ERV3) and HERV-E(4-1) (Katsumata et al, 1998;Andersson et al, 2002;Svensson et al, 2001); an HERV-E element mapping to 17q11 is preferentially expressed in thyroid and pancreas (Shiroma et al, 2001). Most noticeably, the retroviral envelope protein Env T in thyroid is a unique instance of specific expression in a healthy organ, and it may be associated with the hormone-producing status of the tissue (De Parseval et al, 2003).…”
Section: Endocrine Modulation Of Ervsmentioning
confidence: 99%
“…Nonetheless, retroviral genes are frequently expressed in normal and transformed human tissues. The function of these genes in normal human cell physiology is still unclear (32). So far, only the expression of the env gene of HERV-W is known to have a crucial function in normal organismal physiology, namely human trophoblast cell fusion and differentiation (5,12,23).…”
mentioning
confidence: 99%